Mountain guide as a profession of special management and quality supervision in the field of public health and safety - Borek, Dominik; Raniszewski, Szymon; Tomanek, Mateusz; Bugajska, Małgorzata (Journal of Education, Health and Sport, 2023)
The article deals with aspects of quality management by those in the public trust profession of mountain guide. In particular, the article will raise aspects of quality in terms of public health and safety. These two aspects are very important in the work of a mountain guide, who is the person in charge of the group he or she is guiding in mountain areas. These areas can often cause some difficulties for tourists, hence the important role of the mountain guide person to ensure safety during mountain expeditions. Within the framework of the article, the organizational basis for conducting business as a mountain guide will be discussed, and the issue of quality will also be pointed out with regard to the professional self-government of mountain guides, for the establishment of which there have been calls for years. The paper uses a dogmatic and exegetical research method, which required an analysis of the detailed legal regulations of the area, as well as an empirical study of the professional self-government. The article presents the personal views of the authors and cannot be interpreted as the position of any body, entity or institution. The article presents the legal status as of 01/01/2023.